Perinatal and postnatal exposure to phthalates and early neurodevelopment at 6 months in healthy infants born at term - Lucaccioni, Laura; Palandri, Lucia; Passini, Erica; Trevisani, Viola; Calandra Buonaura, Filippo; Bertoncelli, Natascia; Talucci, Giovanna; Ferrari, Angela; Ferrari, Eleonora; Predieri, Barbara; Facchinetti, Fabio; Iughetti, Lorenzo; et al. (Frontiers in Endocrinology, 2023)
Background: Phthalates are non-persistent chemicals largely used as plasticizers and considered ubiquitous pollutants with endocrine disrupting activity. The exposure during sensible temporal windows as pregnancy and early childhood, may influence physiological neurodevelopment. Aims and Scope: The aim of this study is to analyze the relationship between the urinary levels of phthalate metabolites in newborn and infants and the global development measured by the Griffiths Scales of Children Development (GSCD) at six months. Methods: Longitudinal cohort study in healthy Italian term newborn and their mothers from birth to the first 6 months of life. Urine samples were collected at respectively 0 (T0), 3 (T3), 6 (T6) months, and around the delivery for mothers. Urine samples were analyzed for a total of 7 major phthalate metabolites of 5 of the most commonly used phthalates. At six months of age a global child development assessment using the third edition of the Griffith Scales of Child Development (GSCD III) was performed in 104 participants. Results: In a total of 387 urine samples, the seven metabolites analyzed appeared widespread and were detected in most of the urine samples collected at any time of sampling (66-100%). At six months most of the Developmental Quotients (DQs) falls in average range, except for the subscale B, which presents a DQ median score of 87 (85-95). Adjusted linear regressions between DQs and urinary phthalate metabolite concentrations in mothers at T0 and in infants at T0, T3 and T6 identified several negative associations both for infants’ and mothers especially for DEHP and MBzP. Moreover, once stratified by children's sex, negative associations were found in boys while positive in girls. Conclusions: Phthalates exposure is widespread, especially for not regulated compounds. Urinary phthalate metabolites were found to be associated to GSCD III scores, showing inverse association with higher phthalate levels related to lower development scores. Our data suggested differences related to the child’s sex.